Present Trends of Biofuel Production and Consumption in the European Union - Hasan, Morshadul; Oláh, Judit (Journal of Central European Green Innovation, 2022)
Biofuel is one of the trending research areas in the production and consumption economy. Based on the significance of biofuels, this study specifies the objective to explore and discuss the present trends of biofuel production and consumption in European Union listed countries. A descriptive data analysis technique is conducted here using the data from the BP Statistical Review of World Energy, European Union energy annuals, RES Barometer, and STATISTA databases. This study finds that among the 27 EU countries, Austria, Belgium, Bulgaria, Finland, France, Germany, Hungary, Italy, Netherlands, Poland, Portugal, Spain, and Sweden are highly concerned regarding biofuel production and consumption. Due to the unavailability of balanced yearly data, different years’ data are used here to conduct the descriptive analysis. Germany and France are in the leading position in biofuel economic circumstances, particularly from both biofuel production and consumption perspective. It is also found that sugar beets, corn, and wheat are the most used feedstock used for biofuel production, and transportation is the largest source of biofuel consumption.